ROLE OF LIPOPOLYSACCHARIDES AND ENDOTOXEMIA IN PERIODONTITIS. A NARRATIVE REVIEW - Liliana Pasarin; Maria-Alexandra Martu; Ancuta Goriuc; Cristina Popa; Odette Luca; Irina-Georgeta Sufaru; Ruxandra Stan; Silvia Martu; Ionut Luchian (Romanian Dental Association for Education, 2022)
Periodontitis patients are known to have increased circulating lipopolysaccharide activity and metabolic disturbances, which may be either the cause or effect of endotoxemia. This review approaches endotoxemia as a possible molecular mediator between periodontitis and increased risk of cardiometabolic disorders. Observations that bacteria disseminate into circulation after toothbrushing and periodontal procedures and assumptions that endotoxin may disseminate through inflamed periodontium and bleeding gums support the idea of endotoxemia in periodontitis. However, the evidence that periodontitis-associated dysbiosis contributes to endotoxemia is not as strong as in the case of gut microbiome dysbiosis. We describe the structure-function relationship of lipopolysaccharide, the local and systemic inflammatory and immunological responses caused by lipopolysaccharide, current knowledge on endotoxemia in periodontitis, factors affecting the levels of endotoxemia, and its relation to cardiometabolic disorders. They are physically, microbiologically, and biochemically connected to each other, and only crumbs of information are known about this connection. Although the causality is insufficiently demonstrated thus far, many studies have associated changes of the gut microbiome composition, function, and specific bacterial metabolites with cardiometabolic diseases, whereas research on the oral microbiome has severely fallen behind.